2021
DOI: 10.1007/s00425-021-03709-x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the auxin–cytokinin homeostasis in adventitious root formation of rose cuttings as affected by their nodal position in the stock plant

Abstract: Main conclusion Enhanced levels of indole-3-acetic and raised auxin to cytokinin ratios in the stem base contribute to the positive acropetal gradient in rooting capacity of leafy single-node stem cuttings of rose. Abstract Cuttings excised from different nodal positions in stock plants can differ in subsequent adventitious root formation. We investigated the involvement of the auxin–cytokinin balance in position-affected rooting of Rosa hybrida. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 58 publications
3
11
0
Order By: Relevance
“…The average number of roots, root length, and biomass were higher in the apical segments than in the medium and basal segments. Similar results have been reported for the Rosa hybrid [ 83 ]. In contrast, another report observed no significant difference in rooting rate when the cuttings were collected from different positions along with the donor plants [ 84 ], indicating that the rooting potential of the cutting is significantly affected by the physiological state of the explants used in the experiment.…”
Section: Discussionsupporting
confidence: 90%
“…The average number of roots, root length, and biomass were higher in the apical segments than in the medium and basal segments. Similar results have been reported for the Rosa hybrid [ 83 ]. In contrast, another report observed no significant difference in rooting rate when the cuttings were collected from different positions along with the donor plants [ 84 ], indicating that the rooting potential of the cutting is significantly affected by the physiological state of the explants used in the experiment.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the TS lighting resulted in the greatest light efficiency, which further induced well-developed terminal buds and lateral buds, causing higher bio-activities and promoting phytohormone cycles. Meanwhile, the well-developed lateral shoot preferentially receives branch-promoted hormones such as cytokinins transported from the root, thus promoting the quantity and quality of the lateral buds [ 46 , 47 , 48 ]. In addition, according to the nutrition theory that K. Gerber proposed, the well-developed bud cells rapidly grow, vigorously metabolize, and require more nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was found that the lateral buds were able to grow when the cytokinin was applied to the inhibited lateral buds, and the apical dominance was relieved. Therefore, an inhibition of the lateral buds occurred, because they did not have enough cytokinins directed toward them [ 61 , 62 , 63 ]. In our study, the chrysanthemum plants grown using the side lighting lacked light from the top and experienced a stunted development of the terminal bud.…”
Section: Discussionmentioning
confidence: 99%